(untitled) (Global Journal of Science Frontier Research, 2012)
A mathematical model with concentrated parameters of L-lyzin biosynthesis process during continually cultivation of the Brevibacterium flavum type microbial population is proposed. A parametrical identification of the model’s kinetic variables is carried out. A mathematical model with distributed parameters of the same biotechnological process is developed. The stability of the stationary solutions of the obtained dissipative structure is investigated.